The Influence of Accelerometer Epoch Length on Associations of Physical Activity Intensity and Volume with Bone Outcomes. - Skinner, Annie M.; Rowlands, Alex V.; Vlachopoulos, Dimitris; Barker, Alan R.; Janz, Kathleen F.; Moore, Sarah A. (Journal of Sports Science & Medicine, 2023)
Two accelerometer metrics (intensity-gradient and average-acceleration) can be used to determine the relative contributions of physical activity (PA) volume and intensity for health, but it is unknown whether epoch length influences the associations detected. This is important when considering bone health, as bone is particularly responsive to high intensity PA, which may be underestimated by longer epochs. This study aimed to assess the associations between average-acceleration, a proxy measure of PA volume, and intensity-gradient, reflective of PA intensity distribution, from PA data from 1-s to 60-s epochs at age 17 to 23 years with bone outcomes at age 23 years. This is a secondary analysis of 220 participants (124 females) from the Iowa Bone Development Study, a longitudinal study of bone health from childhood to early adulthood. Accelerometer-assessed PA data, captured at age 17 to 23 years, were summarised over 1-s, 5-s, 15-s, 30-s, and 60-s epochs, to generate average-acceleration and intensity-gradient from each epoch length, averaged across ages. Regression analysed associations between mutually adjusted average-acceleration and intensity-gradient with dual-energy X-ray absorptiometry assessed total-body-less-head (TBLH) bone mineral content (BMC), spine areal bone mineral density (aBMD), hip aBMD, and femoral neck cross-sectional area and section modulus at age 23 years. Intensity-gradient was positively associated with TBLH BMC in females, with spine aBMD in males, and with hip aBMD and geometry in both sexes, when a 1 to 5-s epoch was used. Average-acceleration was positively associated with TBLH BMC, spine aBMD and hip aBMD in males, generally when the adjustment for intensity-gradient was from > 1-s epochs. Intensity and volume were important for bone outcomes in both sexes and males, respectively. A 1 to 5-s epoch length was most appropriate to assess the mutually adjusted associations of intensity-gradient and average-acceleration with bone outcomes in young adults.